A case report of multiple relapses of Henoch-Schonlein purpura - Afrilia Intan Pratiwi; Sumadiono Sumadiono; Mei Neni Sitaresmi (Paediatrica Indonesiana, 2023)
Henoch-Schonlein Purpura (HSP) is an acute immunoglobulin A (IgA)–mediated disorder characterized by generalized vasculitis. HSP commonly occurs in children. The annual worldwide incidence is 13-20 per 100,000 children under 17 years of age.1–3 It is characterized by non-thrombocytopenic palpable purpura mostly located on the dependent parts like lower extremities and buttocks, arthralgia/arthritis, bowel angina, and hematuria/proteinuria. HSP pathophysiology is not yet completely understood. Genetic factors are thought to drive the fundamental susceptibility and clinical manifestations. Proposed triggering factors include upper respiratory tract infections, medications, vaccinations, and malignancies. Disease course is usually benign and self-limited. Even though the prognosis is generally good, recurrences or relapses are common within 1 year of initial presentation.4